Fathers detained, contact restrained: Experiences of Palestinian children visiting their fathers in Israeli detention. (October 2019) - Saleh, Mahasin F.; Rabaia, Yoke; Balsam, Corey; Amro, Zeina; Kassis, Samar; Giacaman, Rita
Abstract: Background: Very little is known about the experiences of children of political prisoners internationally, because of the challenges of researching within politically oppressive contexts. Objective: The aim of this secondary analysis was to explore and understand Palestinian children's experiences visiting their fathers in Israeli detention. Participants, setting and methods: Qualitative data from sixteen in-depth interviews with thirty-one children were analyzed. Structural and longitudinal coding cycles were employed and focused upon the timeline of the visitation process. Results: Three overarching themes emerged, which included: Children's experiences 'before the visit', 'during the visit', and 'after the visit'. Subthemes related to the distressing and at times traumatic experiences the children suffered throughout the process of preparation for, going through, and the aftermath of the visit. This included reports of experiencing punitive measures at checkpoints and waiting areas and humiliation and maltreatment by the Israeli authorities during the visitation process. These findings are discussed with reference to the United Nations Convention on the Rights of the Child. It was clear that the children's best interests were denied and contact and interaction with their fathers was restrained under the Israeli visitation scheme. Despite the arduous visitation process that children often hated, they loved to see their fathers. Conclusions: Even though the children's rights were infringed upon, they still endured hardships to maintain whatever contact was possible. International advocacy for the realization of the 'rights of the child' for Palestinian children, as well as other children of political detainees is warranted.